REPRESENTATIF SAHABAT MENYENANGKAN DALAM TVC OREO SEBAGAI MARKETING COMMUNICATION STRATEGY - Lim Yudhi (SEMIOTIKA: Jurnal Komunikasi, 2015)
In mid August 2015, the world was hit by an advertisement that is unique in terms of the song until the very interesting visualization. Oreo miraculous fever hit several countries. Oreo ad that aired in several countries accompanied by the translation of the lyrics of the songs contained in the Oreo ad. Selection of the characters used in the ad interesting. One of the countries that serve such ads is Indonesia. In Indonesia, Oreo ads with the theme of "wonderfilled" that aired in two versions. The first version is ad featuring the figure of sharp-toothed sharks scary. The second version is ad featuring the figure of the vampire (Dracula) are creepy. In both versions of Oreo ad "wonderfilled" told that the characters have a sinister character is transformed into a friendly and pleasant character after they eat Oreo. Ad serving is accompanied by follow-up in the form of an event that invites citizens of Jakarta, capital of Indonesia which has a tropical climate. Residents are invited to imagine what would happen if the Oreo given to Jakarta. In the event, there are lots of games, music and snacks that use Oreo. The event closed with the peak of the "Jakarta snowing". Oreo ad serving "wonderfilled" although there are several versions, still has a consistency which emphasizes the gimmick products. Meaning representation pleasant companions illustrated through a series of scenes in the ad. The message conveyed by these ads is one way to socialize marketing campaigns conducted by Oreo. The unit of analysis in this study are some of the scenes contained in the advertisement oreo "wonderfilled" version of the shark and the vampire. By using the theory of marketing communication, this study tries to see the representation of the meaning contained in the advertisement Oreo through Peirce semiotic analysis and see how they related to the marketing communication strategy. Keywords: Advertising, Oreo, gimmick, representation, semiotics, marketing communication strategy